Phase-sensitive dynamic micro-optical coherence tomography for high-speed intracellular motion imaging - Schulz-Hildebrandt, Hinnerk; Gardecki, Joseph A; Miller, Tiffany; Avila-Wallace, Maria; Villareyna-Lopez, Erica; Tearney, Guillermo (Optics letters, 2025)
Dynamic optical coherence tomography with micrometer resolution (DµOCT) offers enhanced contrast information by evaluating time-dependent signal fluctuations in images of living tissue. DµOCT's use has been limited to imaging excised fresh tissue specimens or 3D cell cultures due to the long observation times required, typically ranging from 1.35 to 25 seconds. To reduce the time needed to obtain DµOCT images, we developed a phase-based algorithm that analyzes intracellular motion by measuring phase changes between adjacent B-scans. This approach significantly reduces imaging time to as low as 40.5 ms while providing a quantitative measure of intracellular motion.